International Business in Conflict Zones: The Case of MTN - Omoola, Sodiq (2022)
It is common for multinational companies to establish subsidiaries outside their home countries and especially in developing regions to tap into emerging markets. It is however a different situation when multinationals establish businesses in unstable and violence-affected regions to take advantage of the local market structure that has suffered a hit by the continuous conflict. Some of these companies are also able to utilize international incentives from development financial institutions. However, running a business in such regions may lead to distortion of the administration of these firms due to the violence which may destroy infrastructure and harm employees. Many Firms are discouraged from investing in conflict zones because of the exposure to insecurity and violence. Notwithstanding, businesses that wish to continue operating in violence-affected regions are required to stay away from dealings that lead to, encourage or promote violence in the region. This paper while reviewing the existing literature on the establishment and operation of a business in conflict zones, examines the operations of the subsidiaries of the South African MTN Group in Afghanistan and North-eastern Nigeria, their alleged involvement in the conflict and the impact on the business operations in the respective regions.